2016
DOI: 10.1088/0953-2048/29/5/053001
|View full text |Cite
|
Sign up to set email alerts
|

Progress in nonmagnetic impurity doping studies on Fe-based superconductors

Abstract: We review the progress of nonmagnetic impurity doping study on the Fe-based superconductors.On the theoretical side, two highly potential candidates for the pairing symmetry order parameter, i.e. the multi-gap s++ and s± wave models, have been proposed but continuously debated. The debate arises because of the complex gap structure, exceptive magnetic and metallic behaviors of Fe-based superconductors which may make the influences of nonmagnetic defects varied in chemical potential, impurity disorder, inter-an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 116 publications
2
19
0
1
Order By: Relevance
“…The s symmetry associated to interband interactions between hole and electron pockets mediated by spin fluctuations, which lead to a superconducting order parameter that changes sign over the Fermi surface sheets, is most often used to describe iron pnictides. The theoretical consequences are found to be consistent with most experiments that investigate the role of pair-breaking effect by impurities 46 . Indeed, despite earlier experiments 78,81,82,83 claimed that the rate of Tc suppression by disorder was much slower than what predicted by the s scenario 84 , later theoretical works dealing with multiband s superconductivity considered different types of impurity scattering potential (finite-ranged potential, different ratios of inter-band to intra-band contributions …) and demonstrated that results for the s± state are not inconsistent with experimental data.…”
Section: Analysis Of Tc Versus Disorder 2a Comparison Between Diffesupporting
confidence: 80%
See 1 more Smart Citation
“…The s symmetry associated to interband interactions between hole and electron pockets mediated by spin fluctuations, which lead to a superconducting order parameter that changes sign over the Fermi surface sheets, is most often used to describe iron pnictides. The theoretical consequences are found to be consistent with most experiments that investigate the role of pair-breaking effect by impurities 46 . Indeed, despite earlier experiments 78,81,82,83 claimed that the rate of Tc suppression by disorder was much slower than what predicted by the s scenario 84 , later theoretical works dealing with multiband s superconductivity considered different types of impurity scattering potential (finite-ranged potential, different ratios of inter-band to intra-band contributions …) and demonstrated that results for the s± state are not inconsistent with experimental data.…”
Section: Analysis Of Tc Versus Disorder 2a Comparison Between Diffesupporting
confidence: 80%
“…Clearly, the curves are spread over a wide range, as also evidenced in the review of ref. 46 . This spread may be explained by the different compounds, different types of irradiations, different doping levels, different pristine Tc0's, magnetic or non magnetic scattering.…”
Section: B Comparison Between Different Routes To Extract the Pairmentioning
confidence: 99%
“…With substitution of atomic impurities into the superconducting Fe 2 As 2 layers, the impurities are found to enhance the ATR phenomenon as introduced above. Substituting magnetic Co and nonmagnetic Zn onto the Fe-site in the Fe 2 As 2 layers, the impurity ions can suppress the superconductivity within a region of a coherence length 22,24,25,35 , and then disorganize the superconducting distribution. Particularly, the impurity scattering centers are aligned with a certain direction, for instance the antiferromagnetic a -axis, resulting in highly anisotropic impurity states 36 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the isotropic s ‐wave superconductors are sensitive to magnetic and resistant against nonmagnetic impurities. Such distinction in the impact of impurities or controlled disorder, when observed experimentally on a new type of superconductor, gives a tentative hint on the underlying pairing symmetry and superconducting mechanism .…”
Section: Introductionmentioning
confidence: 95%